SISTEM PAKAR PENENTUAN TANAMAN PALAWIJA YANG COCOK TUMBUH PADA SUATU DAERA MENGGUNAKAN ALGORITMA FORWARD CHAINING - Yusran Timur Samuel; Yank Nekmese K.; Raymond Maulany (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
Farmers often have Difficulties regarding what crops are suitable for planting in their agricultural areas. For this reason, an expert system application is needed that can help farmers determine what crops can be planted on their agricultural land. This study uses a forward chaininig algorithm expert system method with height attributes, temperature, soil ph, rainfall, Intensity of irradiation, and humidity The expected output is information on what crops are suitable for planting on their agricultural land based on the attributes that are input. In this study researchers used the System Development Life Cycle (SDLC) method in designing expert system applications. The knowledge base used in this study is the result of interviews with experts coup/ed with theories obtained from various literature. Testing the performance and performance of applications using the blackbox method with the conclusion that the system can perform its functions properly and as expected